(untitled) (Asian Journal of Medical and Biological Research, 2020)
Nijhum dwip is a well-known island in which local people are mostly dependent on fisheries resources. The island is located in Hatiya Upazila under Noakhali district, Bangladesh. The present study attempted to investigate the socio-economic condition of fishers on this island. We randomly selected 50 fishers for an interview in the field survey. From the investigation, we found that 94% of fishers were male, and 6% were female. A large portion was Muslim (90%), and the rest was Hindu (10%). About 91% were found married. Nuclear families were more (59%) common compared to joint families. Among school-going children, 57% of boys and 43% of girls were dropouts. Eighty-eight per cent of dwellings were full katcha while semi-pacca were 12% and all the family are lack of electricity facilities. Different types of the net including the set bag net, tong jal, current jal, tanajal etc. were found on this island. They used motorboats, and engine power ranges from 8 to 22 hp for fishing. A group of fishermen caught fish averagely 35-80 kg per day. A portion of them being consumed for households and the rest of them are usually sold. The monthly average income was around BDT7000-8000. Fifty-six per cent of the fishermen borrowed money from money lenders and 44% from the NGOs. Our findings suggest that GOs and NGOs should come forward for the betterment of socio-economic condition through increasing educational opportunities, loan facilities and electricity facilities and sustainable livelihood in the present study area. Asian J. Med. Biol. Res. June 2020, 6(2): 351-358